Shadows of night : the hidden world of the little brown bat - Bash, Barbara (San Francisco : Sierra Club Books for Children, 1993)
Describes the life cycle, physical characteristics, and habits of the little brown bat, one of the most widespread bats in North America.
Publisher's Weekly
Booklist
Library Talk
K-3.
Keywords: Little brown bat -- Juvenile literature; Little brown bat; Bats; Little brown bat; Bats